Analysis of methodology section in empirical research articles by the non-native english speakers in Malaysia - Nor Azma, Manan (Universiti Malaysia Sarawak, UNIMAS, 2009)
Presently, not much research has focused on the methodology section in research articles. Researchers like Brett (1994), Nwogu (1997), Bloor (1998), Lim (2006), and Bruce (2008) advocate further research to analyze this particular section. The aim of this study was to identify the generic structure and the language features of the Methodology section in Non-Native English Speakers‟ (NNES) research articles. The objectives of this study were to: (1) identify the ways on how the existing NNES researchers‟ structuring of their Methodology section in research articles; (2) to determine the frequency and the use of passive and active voice in Methodology section; and (3) to determine the frequency and functions of first personal pronouns in Methodology section. 50 research articles produced by the local NNES researchers were analyzed. For the structure, analysis using Lim‟s (2006) framework revealed that only 42% of 50 research articles follow the typical conventions proposed by Lim (2006), which is describing data collection procedures (Move 1), delineating procedures of measuring variables (Move 2), and elucidating data analysis procedures (Move 3). For the language features, 61.18% of the research articles preferred to use active voice rather than passive voice in constructing the Methodology section. Analysis of the functions of first personal pronouns using Kuo‟s (1999) framework showed that „Explaining what was done‟ was the function that most frequently used in the Methodology section from the research articles studied. Several shortfalls were identified from the analysis. For generic structure, elucidating data analysis procedures (Move 3) was often omitted. The results indicated the need to extend the use of first personal pronouns to other higher level functions, such as „Proposing the theory‟ and „Comparing approaches‟. These findings provide areas to focus on in research writing courses.